PENGABDIAN KEPADA MASYARAKAT MENGENAI PEMBUATAN SABUN CAIR CUCI TANGAN DARI EKSTRAK BUAH ANGGUR (VITIS VINIVERA L.) - Ani Haerani; Wina Wartini; Nathania Alyabasya G; Anggi Dwi Astuti Astuti; Dea Fitriani; Novy Irahmah; Fani Pratama Putra; Rizky Mutakin (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Study of the formulation of handwash liquid soap containing grape extract (Vitis viniveraa L.). Community service aims to produce a stable formulation of liquid hand washing soap containing grape extract (Vitis vinivera L.). This community service is carried out at SMK PGRI 2 Cimahi. This process was carried out using several storage methods, namely organoleptic parameters, pH test and foam test. Organoleptic test analysis on the first day of making hand washing liquid soap for up to 7 days and still in good condition and the last one is the foam test, hand washing liquid soap on the 7th day it still had thick foam. Therefore, it can be said that hand washing soap containing grape extract (Vitis vinivera L.) is good and stable because it gets maximum results.